On a Trivial Family of Noncommutative Integrable Systems - Tsiganov, A.V. (Symmetry, Integrability and Geometry: Methods and Applications, 2013)
We discuss trivial deformations of the canonical Poisson brackets associated with the Toda lattices, relativistic Toda lattices, Henon-Heiles, rational Calogero-Moser and Ruijsenaars-Schneider systems and apply one of these deformations to construct a new trivial family of noncommutative integrable systems.